Antimicrobial bentonite by the addition of geranyl acetate for aflatoxin B1 adsorption (Research, Society and Development, 2022)
A nanocomposite composed of organophilic bentonite (OB) with geranyl acetate (GA) was prepared on a shaker for 1 hours, 180 rpm and room temperature, being subsequently dried an oven at 90 ºC±2 ºC during 48 hours. This material was then characterized for its antibacterial against Staphylococcus aureus and Escherichia coli and antifungal activity against Aspergillus flavus and Aspergillus niger, respectively. Moreover, the adsorption capacity of OB and OB/GA was evaluated using Aflatoxin B1 in the concentration of 107 µg∙L-1. After 17 h, the composite removed a significant amount of mycotoxin, being below 20 µg∙L-1. The results showed that this composite has a good adsorption capacity, can be effective in the removal of mycotoxin in aqueous media and excellent antibacterial and antifungal activity.